2009
DOI: 10.1111/j.1472-765x.2009.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Tn916-like element inStreptococcus parauberisserotype II strains isolated from diseased Japanese flounder

Abstract: Aims:  To screen for the existence and determine the structure of Tn916‐like element in Streptococcus parauberis serotype II strains isolated from cultured Japanese flounder in western Japan. Methods and Results:  In this study, the structure of Tn916‐like element and the flanking regions were characterized by polymerase chain reaction (PCR) and inverse PCR, followed by cloning and sequencing. The Tn916‐like element is 18 031 bp in length and composed of 22 ORFs. Southern blot hybridization analysis showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In this study, tet (M) was detected in 60% of the II isolates and only in 1.6% and 0% of the Ia and Ib/Ic isolates respectively. Interestingly, 95.2% of the Ia isolates contained tet (S), which is similar to the findings of a previously published report (Meng et al, 2009). The mechanism of tetracycline resistance mediated by the tet (M) and tet (S) genes are similar ways, because tet (S) has 78% level of amino acid sequence identity to the tet (M) gene (Roberts, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, tet (M) was detected in 60% of the II isolates and only in 1.6% and 0% of the Ia and Ib/Ic isolates respectively. Interestingly, 95.2% of the Ia isolates contained tet (S), which is similar to the findings of a previously published report (Meng et al, 2009). The mechanism of tetracycline resistance mediated by the tet (M) and tet (S) genes are similar ways, because tet (S) has 78% level of amino acid sequence identity to the tet (M) gene (Roberts, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Except for elements from the Tn916-Tn1545 family which were broadly reported in different streptococcal species originating from diverse animal hosts (9,94,170,196), ICEs carrying resistance genes have rarely been reported in streptococci from animal origin. Indeed, only the mosaic tet(O/W/32/O) carried on ICESsu32457 in S. suis, which could then be transferred to S. pneumoniae, S. pyogenes, and S. agalactiae (197), as well as the lincomycin-resistance gene lsa (192) such MGEs.…”
Section: Role Of the Ices In The Evolution Of Resistancementioning
confidence: 99%
“…Meng et al (2009a) found that a serotype II S. parauberis strain isolated from olive ounder contained both Tn916-like elements encoding tet(M). Similarly, Meng et al (2009b) found that all serotype II strains carried tet(M) and both integrase (int) and excisase (xis) genes were detected, suggesting the presence of a Tn916-like element. In this study, serotype II was represented by 21 of 296 S. parauberis isolates from Korean cultured olive ounder, 17 of which were found to have tet(M).…”
Section: Epidemiological Cut-off Values and Mar Indexmentioning
confidence: 83%